PEMBUATAN NOMOR INDUK BERUSAHA (NIB) UNTUK KESADARAN LEGALITAS USAHA BAGI UMKM KELURAHAN DUKUH SUTOREJO - Diana, Laksmi; Akbhari, Izzatira; Fadhilah, Ariqotul; Hidayaturracman, Hammada (CV. Era Digital Nusantara, 2022)
At this time, Dukuh Sutorejo Village experienced an increase in the number of UMKM. In 2021 the number of UMKM was recorded to reach 1,070 UMKM, this is due to the increasing number of people who want to open their own businesses due to the Covid-19 pandemic where many employees have been laid off by the company, it is difficult to find new jobs, and other problems. However, there are still many UMKM actors in the Dukuh Sutorejo Village area who do not know and understand the importance of business legality in this case the creation of a Business Identification Number (NIB), because some people have an understanding that managing business permits and legality is a complicated matter and takes a long time. Meanwhile, the Business Identification Number (NIB) itself plays an important role in the efforts of business actors. There are many advantages to having a Business Identification Number (NIB), one of which is the legality of the business. Issuance of Business Identification Number (NIB) can be done through OSS (Online Single Submission). The purpose of this Community Service activity is so that UMKM actors in Dukuh Sutorejo Village, Surabaya can understand and know how to make business licenses through OSS and have business legality, in this case in the form of a Business Identification Number (NIB). The method used in this community service activity is to educate about the procedures for making Business Identification Number (NIB) and it is carried out using the door to door method where this activity is carried out by visiting the residence of each UMKM in the Sutorejo Hamlet area. The result of this community service activity is the issuance of a Business Identification Number (NIB) for UMKM actors in Dukuh Sutorejo Village.